Chemical and Antioxidant Properties of Broccoli Growing in Bangladesh - Jahan, Ismet Ara; Mostafa, M; Nimmi, Ishrat; Hossain, M Hemayet; Ahsan, Moinul; Chowdhury, Jasim Uddin (Dhaka University Journal of Pharmaceutical Sciences, 2011)
Broccoli (Brassica oleracea var. italica) a cruciferous vegetable growing in Bangladesh was investigated to determine the fatty acid components, elemental concentrations, ascorbic acid content and antioxidant activity. A total of fifteen compounds were identified from the methylated esters of the fatty acids of flower and stem of broccoli when analyzed by GC-MS. The major compounds were linoleic acid, palmitic acid. linolenic acid, oleic acid, stearic acid and myrestic acid. Elemental analysis was done by XRF method which showed that both the flower and stem contained a significant amount of Na, K, Ca, Mg, Fe, P and Cl. However, heavy metals were not found in any of the broccoli samples. The broccoli flower and stem contained 42.20±0.263 mg and 120±0.254 mg of ascorbic acid per 100g of fresh samples. The methanol extract of broccoli exhibited the highest DPPH radical scavenging activity among methanol, acetone and water extracts. The indegenous broccoli was found to have highest DPPH radical scavenging activity (> 90%) which was comparable to standard ascorbic acid (98.22±1.122%) and BHA (96.01±0.983 %). Methanol extract of flower and stem exhibited highest ferrous ion chelating ability ((91.85±0.951 and 97.38±1.241) respectively whereas the ascorbic acid and BHA hardly demonstrated any ferrous ion chelating ability. These results clearly indicated that Bangladeshi broccoli has a significant potential for uses as nutrients and antioxidant suppliments. Key words: Broccoli; Fatty acids; Minerals; Vitamin C; Free radical scavenging power; Reducing power; Ferrous ion chelating ability. DOI: 10.3329/dujps.v9i1.7427 Dhaka Univ. J. Pharm. Sci. 9(1): 31-37 2010 (June)